SEMANTIC CHANGE OF THE WORD MEANING IN ENGLISH AND UZBEK LANGUAGES - Qosimova, Feruzaxon; Xomidova , O‘lmasxon Ikromjon qizi (Educational Research in Universal Sciences, 2023)
This article is devoted to combinatorial semasiology and pecularities of the process that is known as semantic change.